2006
DOI: 10.1172/jci25705
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes limit tumor cell metastasis

Abstract: Previously we observed that neural cell adhesion molecule (NCAM) deficiency in β tumor cells facilitates metastasis into distant organs and local lymph nodes. Here, we show that NCAM-deficient β cell tumors grew leaky blood vessels with perturbed pericyte-endothelial cell-cell interactions and deficient perivascular deposition of ECM components. Conversely, tumor cell expression of NCAM in a fibrosarcoma model (T241) improved pericyte recruitment and increased perivascular deposition of ECM molecules. Together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(241 citation statements)
references
References 46 publications
8
226
0
2
Order By: Relevance
“…Moreover, clusters of fibroblast-like, asmooth muscle actin and desmin-positive cells dissociated from vessel walls were regularly observed in WT, but not in BbKO tumors (Figure 3c). These structures are symptomatic of vessel wall destabilization, and have been associated with reduced neural cell adhesion molecule (NCAM) expression by the tumor cells and metastasis (Xian et al, 2006). Deposition of collagen type I, a prominent component of the RIP1Tag2 tumor stroma (Sugimoto et al, 2006), could be observed in WT, but not BbKO tumors (Figure 3c, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, clusters of fibroblast-like, asmooth muscle actin and desmin-positive cells dissociated from vessel walls were regularly observed in WT, but not in BbKO tumors (Figure 3c). These structures are symptomatic of vessel wall destabilization, and have been associated with reduced neural cell adhesion molecule (NCAM) expression by the tumor cells and metastasis (Xian et al, 2006). Deposition of collagen type I, a prominent component of the RIP1Tag2 tumor stroma (Sugimoto et al, 2006), could be observed in WT, but not BbKO tumors (Figure 3c, bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Several Vegf antagonists have been approved by the US Food and Drug Administration 137 that increase survival in patients with metastatic breast cancer 138 and metastatic colorectal cancer 139 when combined with chemotherapy. The translational promise of this first targeted therapy against the tumour microenvironment, however, is somewhat tempered by emerging instances of resistance to anti-angiogenic therapy 140 , and examples of stromal cell targeting in animal models that unexpectedly resulted in increased invasion 48 or metastasis 141 . These data reinforce the importance of fully understanding the intricacy of cellular interactions in the tumour microenvironment, using approaches discussed in this Review, in order to isolate the cancer cells from their multiple support networks and effectively destroy them.…”
Section: Discussionmentioning
confidence: 99%
“…These examples indicate that it will be important to inhibit mobilized BMDCs alongside drugs that target cancer cells, and this synergy may in fact explain some of the therapeutic efficacy observed in certain combination trials in mice and humans to date. 141 . These data reinforce the importance of fully understanding the intricacy of cellular interactions in the tumour microenvironment, using approaches discussed in this Review, in order to isolate the cancer cells from their multiple support networks and effectively destroy them.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%